Effectiveness of topical silicone gel and pressure garment therapy for burn scar prevention and management in children 12-months postburn: A parallel group randomised controlled trial. (August 2021) - Wiseman, Jodie; Simons, Megan; Kimble, Roy; Ware, Robert S; McPhail, Steven M; Tyack, Zephanie
Objective: The longer-term effectiveness of silicone and pressure burn scar interventions was evaluated at 12-months postburn. Design: Parallel group, randomised trial. Setting: Hospital outpatient clinics, research centre. Participants: Children referred for burn scar management following grafted or spontaneously healed acute burn injuries or scar reconstruction surgery. Interventions: Participants were randomised to: (1) topical silicone gel only, (2) pressure garment only, or (3) combined topical silicone gel and pressure garment. Main measures: Primary outcomes were scar thickness (blinded ultrasound measurement) and itch intensity (caregiver proxy-report, numeric rating scale). Results: Of 153 participants randomised who received the interventions (silicone n = 51, pressure garment n = 49, combined n = 53), 86 were followed-up at 12-months postburn ( n = 34, n = 28, n = 24). No differences were identified for the primary outcomes using intention-to-treat analysis. Scar thickness mean difference (95% confidence interval) = 0.00 cm (−0.04, 0.05); −0.03 cm (−0.07, 0.02); 0.03 cm (−0.02, 0.08) and scar itch = 0.09 (−0.88, 1.06); −0.21 (−1.21, 0.79); 0.30 (−0.73, 1.32) for silicone vs pressure; silicone vs combined and combined vs pressure respectively. No serious adverse effects occurred. Conclusion: Similar to short-term results, the combined intervention offered no statistically or clinically significant benefit for improving the primary outcomes compared to each intervention alone. No differences in the primary outcomes were identified between the silicone and pressure alone groups.